Development of Team Cohesiveness Measurement Instruments in Interprofessional Collaborative Practice in Health Care - francisca sri susilaningsih; Henny Suzana Mediani; Titis Kurniawan (Jurnal Keperawatan Padjadjaran, 2018)
AbstractHealth care management has an obligation to always provide safe, sustainable, comprehensive, quality and satisfactory health care for both the service user and care provider. The management and culture are built through the Interprofessional Health Care Collaborative Practice Model (MPIPK), which are implemented through four model components, i.e. the clinical pathway of patient management, team management of patients, patient care integrated documentation, and interdisciplinary patient problem solving through interdisciplinary case conference forums. In order to realize interprofessional collaboration practices, a cohesive climate is required that supports group functions and performances, and an instrument is needed to measure the team cohesiveness of this model. This research was conducted to develop a team cohesiveness measurement instrument in the interprofessional collaboration of health care. The instrumentation research design was carried out through the following steps: 1) Preparations of the instrument design commenced from the synthesis theory related to collective culture and individual culture on four components of the model; 2) Validation of the contents of the instrument with related experts; 3) Construct validation with 237 healthcare practitioners in an accredited hospital setting. Expert judgment results on instrument relevance (CVI) ranged from 0.77 to 0.91, the essence of instrument contents (CVR) was in range (+) 0.27 - 0.63, CVI and CVR scores indicated the relevant and essential content of the instrument. Test results of all constructed items were valid (0.283 - 0.847) and reliable, α Cronbach on 4 components (0.792 - 0.963) so, it is feasible to be used to measure the team cohesiveness.